Problems Of E-Business Implementation in SMEs - Baršauskas, Petras; Šarapovas, Tadas (Ekonomika, 2004)
The rapid growth of electronic business has been evident since the very beginning of the last decade. Nevertheless, so far companies experience many problems related to the implementation of e-business. This article is focused on the analysis of the main problems as well as opportunities of small and medium-sized companies (SMEs) engaged in e-business. However, in the rush to offer e-business applications to beat competition or to respond to client and internal needs. many businesses have developed unfriendly, expensive. limited services of questionable value. This article will present an analysis and some methodological guidelines as to how to solve the problems arising in the implementation of e-business as well as how to best use the offered opportunities.The main goal of the article is to analyse the problematical issues of implementing e-business in small and medium-sized enterprises.The following objectives are set in the article:1. To define the main problems and barriers in engaging in e-business faced by small and medium- sized enterprises.2. Based on the analysis of survey results. to identify the main reasons and opportunities for involvement in e-business.3. To outline the characteristics that small and medium-sized enterprises should possess in order to be effective in e-business.The following research methods are applied: theoretical and comparative analysis. an empirical study of SMEs on the issue of e-business.